(untitled) (International Journal of Engineering and Computer Science, 2014)
Data transmission through metallic structures is commonly needed in industrial control applications. in an exceedingly range of those applications, mechanically penetrating the structure to pass cables and establish a wired communication link is either impossible or undesirable. Examples of such structures include metal bulkheads, pressure vessels, or pipelines. Ultrasonic communication has been projected as an answer for through-metal information transfer without penetrating the structure. The reverberating nature of the through-metal channel, however, will cause signiﬁcant inter-symbol interference, limiting the info rate possible by conventional single-carrier communication techniques. During this paper, we tend to describe a through-metal communication technique that exploits the slow-varying nature of the ultrasonic channel to implement AN orthogonal-frequency-division multiplexing-based rate-adaptive peak-to-average power quantitative relation (PAPR) reduction algorithm. Measurements of the projected adaptive algorithm have demonstrated transmitted output rates. This improvement provides the desired output and error rate to support high-rate network applications in otherwise data-limited environments.